STRATEGIC MANAGEMENT OF HUMAN RESOURCES IN EDUCATIONAL ORGANIZATIONS - M. Rabee, Ahmad (European Scientific Journal, ESJ, 2014)
The objective of this research is to investigate the possibility ofapplying new innovations in educational organization. University of Jordanwas used as case study as being one of the oldest and pioneer universities inJordan. The research was executed using interviews and seeking materialapproves the innovation process. The results showed that the management ofhuman resources and innovation process can be succeeded on the long run.